Accumulating approach to the life-cycle pension model: practical advantages - Yaniv Azoulay; Andrey Kudryavtsev; Shosh Shahrabani (Financial Theory and Practice, 2016)

(untitled)
In the present study, we make an effort to enhance the practical advantages of the life-cycle pension model. We observe that previous studies are based on a “switching”approach, that is, on the assumption that when a pension fund member reaches a certain age, his accumulated savings are fully switched to another fund with a lower risk profile; we suggest an “accumulating” approach, according to which, at the same age, the member’s previously accumulated wealth continues to be invested in the same fund, while his new regular pension contributions start being directed to another (less risky) fund. We consider a hypothetical (average) Israeli employee, analyze two age-dependent life-cycle investment distributions of his pension savings, and perform a comparison between the two approaches to the life-cycle model by employing an estimation-based and a simulation-based technique. The results demonstrate that the “accumulating” approach provides: (i) higher estimated annualized real returns and real accumulated savings; (ii) significantly higher simulated mean and median values of real accumulated savings. Moreover, we document that, though the “accumulating” approach increases the standard deviation of total savings, it does not lead to critically low pension wealth levels even for relatively unfavorable sequences of financial assets’ returns. Therefore, we conclude that the “accumulating” approach to the life-cycle model has a potential significantly to increase pension fund members’ total accumulated wealth relatively to the common “switching” approach, without significantly increasing the members’ risk.